(untitled) (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2019)
This article investigates two recent developments with potentially important implications for the Iberian sibilants: the apparently systematic correspondence of Iberian s : ś with Basque z/tz : s in the alleged Iberian numbers, and Ferrer i Jané’s proposals of dual systems for ś in the Meridional semisyllabary and s in Levantine. It argues that the identification of the Iberian numbers seems plausible, and that a genetic relationship between Iberian and Basque may indeed be the most likely explanation for the proposed matches, despite widespread scepticism. Ferrer i Jané’s proposed dual systems for the sibilants also appear to be genuine, but the evidence for the Levantine version is highly problematic.